2017
DOI: 10.1039/c7cp00681k
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the molecular interaction between two polyoxygenated cinnamoylcoumarin derivatives and human serum albumin

Abstract: Ligand binding studies on human serum albumin (HSA) are crucial in determining the pharmacological properties of drug candidates. Here, two representatives of coumarin-chalcone hybrids were selected and their binding mechanism was identified via thermodynamics techniques, curve resolution analysis and computational methods at molecular levels. The binding parameters were derived using spectroscopic approaches and the results point to only one pocket located near the Trp214 residue in subdomain IIA of HSA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…On interaction, the polarity around aromatic residues was increased and so the heterocyclic hydrophobic groups of Trp and Tyr residues were exposed to more polar environment. All these observations revealed that the interaction of ID with HSA resulted in conformational changes in HSA …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…On interaction, the polarity around aromatic residues was increased and so the heterocyclic hydrophobic groups of Trp and Tyr residues were exposed to more polar environment. All these observations revealed that the interaction of ID with HSA resulted in conformational changes in HSA …”
Section: Resultsmentioning
confidence: 86%
“…CD spectrum of HSA exhibited two negative bands in the UV region at 208 and 222 nm respectively. These bands appear due to π→π* and n→π* peptide bond transfer respectively and they signify the characteristic α‐helical structure of HSA …”
Section: Resultsmentioning
confidence: 99%
“…ITC experiment was conducted to obtain the quantification of binding affinity and thermodynamic characterization of the binding process . The result of the sequential titrations of SLS into CAT was corrected with the deduction of dilution heats.…”
Section: Resultsmentioning
confidence: 99%
“…ITC experiment was conducted to obtain the quantification of binding affinity and thermodynamic characterization of the binding process. [34] The result of the sequential titrations of SLS into CAT was corrected with the deduction of dilution heats. The plot in Figure 3 was best fitted to the model of two sets of binding sites, suggesting that two types of binding site existed in CAT upon SLS binding.…”
Section: Itc Experimentsmentioning
confidence: 99%
“…The lower panel shows an integrated heat prole that has been appropriately corrected by subtracting the corresponding dilution heats. 22,23 In the lower panel, heat data are plotted against the corresponding molar ratio and tted to a one set of sites model using MicroCal Origin 7.0 soware, which was supplied by the instrument manufacturer. 24 These data can be utilized to calculate the binding constant (K), and the thermodynamics of binding, i.e., enthalpy changes (DH) and entropy changes (DS).…”
Section: Characterization Of the Tgb-hsa And Tgb-bsa Bindingmentioning
confidence: 99%